The implementation of the Policy Area No. 11 Year 2010 about the Education of Madrasah Diniyah Takmiliyah in Bogor Regency - Ridwan Said; Sutaryat Trisnamansyah; Hanafiah Hanafiah; Ahmad Khori (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Government policy number 11 of 2010 about Education Diniyah Takmiliyah implemented in bogor regency has not been run in accordance with what is expected by the stakeholders pendidikan diniyah. So this research aims to obtain a detailed description of how the process of planning, organizing, implementation, monitoring, and evaluation of the implementation of management policy government area is done. This research uses descriptive method with qualitative approach. Based on the results of the research, it is known that the implementation of the regional regulation no. 11 year 2010, MDT does not yet have planning process well in accordance with the rules, the next step in the management of the organization is in compliance with local regulations but not maximum, then the implementation is also still there is a lack of it due to the lack of knowledge of teachers about the science of religion and the qualification level of education, judging from the results of monitoring and evaluation shows the low quality of the educator's resource the MDT that need to be followed up with training programs, mentoring, scholarship program for teachers MDT as well as the fulfillment of the needs of the learning facilities and infrastructure MDT in Bogor Regency